Financial Rasio indicators and profitability in Islamic Bank: The Moderating Effect of Size and Age Bank - Syahadatina, Zahwa; Lestari, Kurnia; Sahliyah, Fatihatus (Journal of Financial and Behavioural Accounting, 2025)
Indonesia's Islamic banking sector demonstrates strong development based on financial performance. This study is to find the effect on return on assets of financial ratios, capital adequacy ratio, non-performing financing, and financing to deposit ratio, using size and age as moderating factors. This will enable one to determine whether age and size of banks affect the correlation between these financial parameters and return on assets. Using secondary data on Islamic commercial banks in Indonesia between 2011 – 2023 with total 119 bank-year observations. This work applies a quantitative research approach. This analysis reveals that despite non-performing financing reduces return on assets, the capital adequacy ratio and financing to deposit ratio improve these indices. By using moderation regression analysis, banks can increase the impact of the financing ratio on deposits and the capital adequacy ratio on return on assets.